Morphological Analysis of Derivational Affixes in Brothers Grimm’s the Story of Rapunzel - Siboro, Efrika; Bram, Barli (ENGLISH FRANCA : Academic Journal of English Language and Education, 2020)
This paper aimed to explore derivational affixes, more specifically the types of derivational affixes and the functions of the derivational affixes in the story of Rapunzel, which was written by the Brothers Grimm. The exploration of the affixes is urgent to conduct because it would assist learners of English in general in enriching their vocabulary items. This study was quantitative descriptive. The researchers collected complex words from the story and analyzed their derivational affixes. Results showed that, first, there existed 33 occurrences of words containing derivational affixes. Four of the 33 words contained three types of prefixes, namely en-, un- and re-, occurring twice, and 29 of the 33 contained suffixes, such as -ful, -ness, -able, -ly, -ing, -ed, -en, -ent, -less, -y, -ous, and -dom. Second, there were four functions of derivational affixes in the story of Rapunzel, namely noun formation, with 10 occurrences (30.4%); adjective formation, with eight occurrences (24.2%); verb formation, with seven occurrences (21.2%); and adverb formation, with eight occurrences (24.2%).Keywords: affix, derivational morphology, prefix